Prosecutorial agency, backlash and resistance in the Peruvian chapter of Lava Jato - Baraybar, V; Gonzalez-Ocantos, EA (Cambridge University Press, 2022)
Peru’s Lava Jato stretched its tentacles widely and ravaged the political establishment. Grand corruption cases present a series of challenges related to how to secure evidence in information-poor and politically hostile environments. Overcoming these challenges without jeopardizing the integrity of the inquiry is no small feat. The tools that prosecutors rely on generate controversy, as well as tensions between effectiveness and due process that are difficult to resolve. Success therefore calls for clever and skillful prosecutors. The analysis digs deep into the dynamics of Peru’s Lava Jato to discuss the nature of these challenges and how prosecutors dealt with them. Contingent choices often determined whether enough evidence came to light, thus widening the window for ambitious investigative efforts. The chapter further looks at the backlash that ensued, how this conditioned prosecutorial efforts, and why investigators were able to mitigate its impact. One interesting feature of Peru’s Lava Jato is that prosecutors not only had to deal with an obstructionist political class, but also with networks of judicial clientelism commanded by senior officials. The chapter traces how rank-and-file prosecutors negotiated such bureaucratic pathologies to protect the inquiry, and discusses the likely impact of these struggles on the future of the case.